2019
DOI: 10.1155/2019/4174985
|View full text |Cite
|
Sign up to set email alerts
|

Giant Protruding Nodular Fasciitis of the Anterior Chest Wall Clinically Mimicking a Soft Tissue Sarcoma

Abstract: Nodular fasciitis (NF) is a benign reactive proliferation of myofibroblasts that predominantly occurs subcutaneously. Commonly, it presents as a rapidly growing swelling in 4-8 weeks. NF mostly occurs in adults aged 20-50 years and usually has a diameter<3‐4 cm. Giant NF with a diameter>4 cm is rare. Owing to its rapidly growing nature, a precise clinical diagnosis is difficult; it is frequently misdiagnosed as an aggressive or malignant tumor. Herein, we present the case of a 15-year-old male who presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It sometimes shows spontaneous regression [6] and recurrence is rare, even after incomplete excision [2], with no reports of malignant transformation. These lesions may show atypia and mitoses, making nodular fasciitis difficult to distinguish from sarcoma [5,[7], [8], [9]]. In fact, Plaza et al [10] reported that two thirds of their cases were misdiagnosed as sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…It sometimes shows spontaneous regression [6] and recurrence is rare, even after incomplete excision [2], with no reports of malignant transformation. These lesions may show atypia and mitoses, making nodular fasciitis difficult to distinguish from sarcoma [5,[7], [8], [9]]. In fact, Plaza et al [10] reported that two thirds of their cases were misdiagnosed as sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…With the rare exception of giant nodular fasciitis [6 , 7] , dimensions are usually below 3-4 centimeters [7] ; history of previous trauma can be referred in a low percentage of cases (10%) [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Nodular fasciitis may occur in every part of the body, presenting elective localization in the upper extremities and trunk [2 , 7 , 14] , as well as head and neck [15 , 16] - the latter, recognizes a particular involvement of infants and children [1] .…”
Section: Introductionmentioning
confidence: 99%